Licit and Illicit Drugs: The Consumers Union Report on Narcotics, Stimulants, Depressants, Inhalants, Hallucinogens, and Marijuana including Caffeine, Nicotine, and Alcohol - Brecher, Edward M. (Little, Brown and Company, 1972)
Contenido: Los Narcóticos: Opio, Morfina, Heroína, Metadona; Cafeína; Nicotina; Alcohol, Barbitúricos, Tranquilizantes y otros Sedantes e Hipnóticos; Coca, Cocaína, Amfetaminas y otros Speeds; Inhalantes, Solventes y Pegamentos; LSD y Equivalentes; Marijuana y Hashish; El Escenario de la Droga.